DESIGN AND SIMULATION OF COCONUT TREE CLIMBING TOOL FOR COCONUT FARMERS IN LOMBOK SANGATTA BAY, EAST KUTAI - Kuswandi Arifin; Suherna Suherna; Alapson Samosir (Journal of Industrial Engineering Management, 2020)
Great potentiality of coconut cannot be separated from the method of coconut harvest which still draw a lot of problems in. Until now, coconut farmers still use climber service in coconut harvesting. The process of coconut tree climbing is usually done without tools. This is very risky for the harvesters. Since the utilization of animal service (monkeys) have already prohibited from commercial activities, human service in coconut tree climbing becomes the alternative for the farmers. For this reason, the aim of this study is to design a tool for coconut tree climbing that will help coconut harvesters in Lombok Sangatta Bay, East Kutai, by considering climber's characteristics. Furthermore, the tool is made in form of design, which then being simulated to determine the tools’ safety level, stress level and the ability which is designed by using SolidWorks 2018 software.The result for the proposed design of coconut tree climbing tool for coconut harvester in Lombok Sangatta Bay, East Kutai, is to use 20 mm x 20 mm x 2 mm of hollow profile with AISI 1020 material built, which is declared safe for 80 kg capacity. The highest score of stress is 223.04 Mpa on body holder, 4.68 mm deflection, 1.6 in factor of safety, and 17.08 kg for tool's overall weight